Retinal fractal dimension analysis at optic nerve head using smartphone-assisted fundus photography on eyes with diabetes mellitus risk factors - Nur Raihan Esa (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Fractal dimension (Df) analysis have been shown as a sensitive measure for charting retinal vascular changes, while smartphone-assisted fundus photography (SAFP) has been demonstrated as a useful tool in screening eyes with problem related to diabetes mellitus (DM). We took these two tools together to investigate the DM risk factors using the best chosen SAFP by measuring the Df. The objectives of this thesis were: (i) to determine the best retinal image of two SAFPs, the Peek Retina™ and 3DPO for Df analysis; (ii) to assess the reliability of Df analysis using the chosen best SAFP; (iii) and to compare the Df of the optic nerve head (ONH) vasculatures between groups with risk- and non-risk of DM: and (iv) to explore the potential association of ONH vasculature's Df with risk factors of DM. For the first objective, our first experiment compared the retinal images between Peek Retina™ and 3DPO. It was determined that PEEK RetinaTM was preferred for retinal vascular tracing work for Df analysis, in comparison to 3DPO. In experiment two, based on the best SAFP in the first experiment finding, we determined the Df analysis reliability using the images taken using Peek Retina™. It was shown that the intragrader and intergraders reliabilities were both in good agreement. Peek Retina™ has shown as a reliable SAFP to evaluate retinal vasculature using Df analysis. For objectives three and four, the ONH vasculatures Df value were analysed in groups with risk and non-risk of DM. The results indicated that the ONH vasculatures Df value was not significantly different between the groups, and there was no associations observed between ONH vasculature Df with DM risk factors. The findings in this thesis advocated that the Peek Retina™ is a reliable tool for the evaluation of retinal vascular Df and may be used in expansion of ophthalmic services in various setting. The result in this study also confirms that changes that due to DM probably occurs in the peripheral vessels, and ONH Df values was not associated with DM risk factors.